2022
DOI: 10.1177/14680181221092682
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of compliance with COVID-19 preventive measures among the public in Qatar and Kuwait

Abstract: Policy responses to the COVID-19 pandemic are assessed by documenting the public’s perception, knowledge, and adherence to preventive behaviors to mitigate the spread of the virus. Using an online survey administered in both Qatar and Kuwait, this article examines the associated state-mandated compliance measures experienced by citizens and expats during the outbreak of COVID-19. The survey measured public attitudes, behavioral responses, and compliance with state-mandated preventive measures. The study showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(120 reference statements)
0
0
0
Order By: Relevance
“…A study in China has found that people who experienced the negative impact of the pandemic on employment and anxiety were more likely to suffer from pandemic fatigue, whereas those in better health were less likely to experience this [30]. The concept of pandemic fatigue and its association with its potential drivers have been addressed to a certain extent in some countries, such as China, Turkey, and the United States, considering the compliance behavior's dependence on the sociocultural contexts [32]. In Japan, a collectivist society that values relationships, pandemic fatigue is especially concerning.…”
Section: Introductionmentioning
confidence: 99%
“…A study in China has found that people who experienced the negative impact of the pandemic on employment and anxiety were more likely to suffer from pandemic fatigue, whereas those in better health were less likely to experience this [30]. The concept of pandemic fatigue and its association with its potential drivers have been addressed to a certain extent in some countries, such as China, Turkey, and the United States, considering the compliance behavior's dependence on the sociocultural contexts [32]. In Japan, a collectivist society that values relationships, pandemic fatigue is especially concerning.…”
Section: Introductionmentioning
confidence: 99%